If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+18=6(3x-9)
We move all terms to the left:
6x+18-(6(3x-9))=0
We calculate terms in parentheses: -(6(3x-9)), so:We get rid of parentheses
6(3x-9)
We multiply parentheses
18x-54
Back to the equation:
-(18x-54)
6x-18x+54+18=0
We add all the numbers together, and all the variables
-12x+72=0
We move all terms containing x to the left, all other terms to the right
-12x=-72
x=-72/-12
x=+6
| 12(15+x)=6x+6 | | 12(x+4)=4x+8 | | 62=-3(5x-1)-1 | | -4(4-3x)=-64 | | 3^n=3/10 | | 4x(7+3x)=28x+12x2 | | n2+12n+20=0 | | 12=k4/5 | | d4=5 | | 138=−2+4(6p+5) | | 70x+4=5 | | F(x)=(x³+2)1/x | | 2x–8=–3x+12 | | x^2-20x+100=8.6 | | 8(x-13)=48 | | 3x+2=-6^(-x) | | 3x+0.4=x+3.8=2x+1.5 | | 3.25+x=(3.25+x)/2 | | 49=0+7y | | 13=5-4d | | 81=9+3y | | 130=5-5y | | 6=2(3y+4) | | 5x^2+4x^2=0 | | 5x²+4x²=0 | | Y=20-z | | F(x)=10x-2x+2 | | Y=20-a | | x-0.1x=96.5 | | x=8x+6≥4x+22 | | 2x6+3x4-1=0 | | 9x^2-17x-360=0 |